‘Beautified With Our Own Feathers’: The Winter’s Tale, Transformative Works, and Fanfiction - Philip Goldfarb Styrt (Ceræ)
The connection between early modern drama and contemporary online fanfiction is frequently mentioned — on both sides — but rarely analyzed in detail. In particular, the rich analytical language developed by online fandom for issues of adaptation, transformation, and intertextuality has been relatively neglected and underutilized by literary scholars. This paper uses William Shakespeare’s The Winter’s Tale and its relationship to Robert Greene’s Pandosto to show how this analytical language can help us better understand the relationship between play, source, and audience in ways that go beyond traditional source analysis. Since the connections between The Winter’s Tale and Pandosto have been extensively studied, what this article contributes is not original research into how Shakespeare used Greene’s play, but rather a new analytical approach that draws on the terminology and approaches of online fandom. In doing so, it demonstrates how we can better understand Shakespeare’s adaptation of Greene through this lens: for example, how the pacing of the play can be viewed as a function of canon-divergent fanfiction, or how the play’s reversal of Greene’s Bohemia and Sicilia relates to alternate universe fanfiction. In demonstrating the usefulness of this new lens for existing observations about the connection between the two works, this article distinguishes the fanfictive reading from other related interpretations, highlighting the value of adding this approach to those already used to analyze early modern texts.